Injectable Nanorobot-Hydrogel Superstructure for Hemostasis and Anticancer Therapy of Spinal Metastasis - Chen, Qing; Yan, Miao; Hu, Annan; Liang, Bing; Lu, Hongwei; Zhou, Lei; Ma, Yiqun; Jia, Chao; Su, Dihan; Kong, Biao; Hong, Wei; Jiang, Libo; et al. (Nano-Micro Letters, 2024)
Surgery remains the standard treatment for spinal metastasis. However, uncontrolled intraoperative bleeding poses a significant challenge for adequate surgical resection and compromises surgical outcomes. In this study, we develop a thrombin (Thr)-loaded nanorobot-hydrogel hybrid superstructure by incorporating nanorobots into regenerated silk fibroin nanofibril hydrogels. This superstructure with superior thixotropic properties is injected percutaneously and dispersed into the spinal metastasis of hepatocellular carcinoma (HCC) with easy bleeding characteristics, before spinal surgery in a mouse model. Under near-infrared irradiation, the self-motile nanorobots penetrate into the deep spinal tumor, releasing Thr in a controlled manner. Thr-induced thrombosis effectively blocks the tumor vasculature and reduces bleeding, inhibiting tumor growth and postoperative recurrence with Au nanorod-mediated photothermal therapy. Our minimally invasive treatment platform provides a novel preoperative therapeutic strategy for HCC spinal metastasis effectively controlling intraoperative bleeding and tumor growth, with potentially reduced surgical complications and enhanced operative outcomes. Highlights: 1 Site-selective superassembly was used to synthesize a nanorobot with bionic rod-shaped head/hollow tail structure, exhibiting strong photothermal effect, high drug loading capacity, precise and controlled drug release, and excellent motility. 2 Injectable regenerated silk fibroin (RSF) nanofibril hydrogels were developed via simple sonication, offering significant production, structural, and performance advantages. 3 Nanorobot/thrombin (Thr)/RSF nanofibril hydrogels reduced intraoperative bleeding of hepatocellular carcinoma (HCC) spinal metastasis, provided starvation embolization, and prevented post-surgery recurrence. 4 Nanorobot/Thr/RSF nanofibril hydrogels inhibited blood supply to residual tumors and reduced neovascularization, inhibiting post-surgery HCC spinal metastasis recurrence.